Frameworks for News Treatment of the Relationship Between the Central Iraqi Government and the Kurdistan Regional Government of Iraq: An Analytical Study in the "Iraqi" and "Rudow Satellite Channels - Ali, Maad Asi (Al-Adab Journal, 2021)
Satellite channels are a major source of news for the public because of the characteristics and characteristics that make it in an advanced position of other media. The history of the relationship between Baghdad and Erbil is fraught with crises over the past decades, but after 2003 and the change of the political system in Iraq, the relationship between the Iraqi central government and the Kurdistan Regional Government (KRG) witnessed a radical change in the relationship. Both governments sought to develop the relationship between the two governments. The establishment of bridges of cooperation between them, and in view of this relationship it was necessary for the media to reflect the distinction of this relationship within the content of the media, and since the emergence of satellite channels, most of the satellite channels, including the Iraqi satellite channel and the channel Rudao to pay attention to private news The two governments to develop a relationship to keep up with international trends in this area, hence this study (to monitor the treatment of the Iraqi satellite channels and channel Rudaw of the relationship between the central government and the provincial government) through the analysis of the content of the study channels in terms of form and content frameworks. In this study, the researcher aimed to achieve a set of objectives of identifying the news frames that dealt with the subject of the study, and determining the size of interest of the two channels in the study subject. And to identify the paths of persuasion used to address the subject of the study. This study falls under the category of descriptive research, which is based on one of the theories of the media that study the relationship between variables and media. The study also relied on the survey methodology to inform both descriptive and analytical aspects of the content of the study channels in terms of form and content, by analyzing the content of the news presented in the two channels during the study period. The study concluded with a number of results, the most important of which were: The study found the polymorphisms and templates that were used in the treatment of the subject of study in the two channels of analysis between news articles, articles of opinion and other news items. - The sources of the news item and the picture used by the two study channels varied between Arab, foreign, electronic and private sources. - The diversity of the type of news content presented in the two channels of study has turned out to be between psychological, economic and social issues. - The personalities in the two channels of study and expressive on the subject of the study between the head of state and ministers of officials and experts, political analysts and spokesmen on behalf of their countries. - The reference frames used by the two study channels were varied in presenting and addressing the subject of the study between a formal, historical, legal and religious framework. The study revealed the difference in the function of the frameworks that were used to introduce and deal with the subject of the study between offering and subtracting the expected and subtracting damages and promoting relations.